VIRTUAL MEDIATION IN DIVORCE CASES AT UJUNG TANJUNG RELIGIOUS COURT - Siti Nur Aisyah (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
The mediation process was initially carried out outside the court institution (non-litigation) for the parties to the dispute, but with the times and changes in behavior, a mediation process was made in court that was inseparable from the court institution (litigation). The mediation process is an obligation that must be carried out by the judge before carrying out the next trial. If you look at PERMA No. 1 of 2016, there are many advantages why mediation is used in court. The purpose of this study is to understand the problems faced in virtual mediation at the Ujung Tanjung Religious Court and describe the efforts made by law enforcement of the Ujung Tanjung Religious Court in handling virtual mediation problems in terms of the effectiveness of Soerjono Soekanto. qualitative approach. The conclusion of this study is that the low success of the community itself is that not all parties in this case use the services of advocates, and the average level of education of the parties is low. The Ujung Tanjung Religious Court in carrying out its duties and functions has carried out a mediation process based on PERMA No.1 of 2016, the results of the litigants in conducting the mediation process are still low and the parties' strong desire to divorce. The Ujung Tanjung Religious Court has made efforts to resolve the issue, but it still requires awareness and responsibility. The online mediation process itself if referring to the Supreme Court Rules, the process can be done using audio-visual media such as video calls that are already available in many applications. In other words, the role or function of this paper is expected to be able to be a social construction to find the level of effectiveness of mediation in divorce cases in religious courts.